Trichinelloscopy of domestic and wild animal carcasses - A. V. Uspensky; O. B. Zhdanova; O. N. Andreyanov; L. A. Napisanova; N. S. Malysheva (Российский паразитологический журнал, 2021)
The purpose of the research is analyze the localization of Trichinella sp. in animals muscle and to evaluate the methods of intravital and post-mortem diagnosis of trichinellosis in domestic, wild and game animals.Materials and methods. In order to prevent trichinellosis in human population and animals, life-time and post-mortem diagnosis methods for trichinellosis are widely used. Life-time diagnosis of trichinellosis is based on detection of specific antibodies in blood serum of sick animals. Modern immunological assays allow detecting specific antibodies (immunoglobulins J and M) at 10–12 days after infection. Enzyme-linked immunosorbent assay (ELISA) with fractionated antigen has the greatest real possibility of application for individual and mass seroepizootic studies of pigs and horses; ELISA is a highly sensitive and specific test. Veterinary and sanitary examination is conducted by methods of compressor trichinelloscopy and peptolysis (muscle tissue digested in artificial gastric juice). For the compression research method, in particular for pig carcasses, 2 samples of the diaphragmatic peduncles of 60 g each are taken. It is also possible to study samples from masticatory muscles, tongue, intercostal space or esophagus. Twelve sections are made from each sample (24 in total). A more sensitive and productive method is the digestion of muscle tissue using a set of diagnostic devices and instruments such as AVT. The method is based on peptolysis of crushed muscle tissue in technological reactors. Diagnosis of trichinellosis using such devices makes it possible to automate and mechanize all processes associated with the isolation of Trichinella larvae. The main application areas of the devices are meat processing factories, fur farms or veterinary and sanitary examination laboratories in the markets.Results and discussion. We presented data on the role of veterinary and sanitary examination for trichinellosis in susceptible animals as the core measure in the system of measures to prevent this infection. We analyzed indicators of diagnostic efficiency, performance and usability of methods of compressor trichinelloscopy and digestion of muscle tissue in artificial gastric juice. Factors of diagnostic efficiency, performance and usability of methods of compressor trichinelloscopy and digestion of muscle tissue in artificial gastric juice were analyzed. Information was given on localization of Trichinella larvae in various species of domestic and wild animals, optimal sampling sites and volumes of muscle tissue samples with the existing methods of examination for trichinellosis. To study fresh carcasses for trichinellosis at meat processing factories, the peptolysis method is recommended.